Ideology and Utopia in China's New Wave Cinema Globalization and Its Chinese Discontents - Wang, Xiaoping (Chinese Literature and Culture in the World, 2018)
Ideology and Utopia in China's New Wave Cinema investigates the ways in which New Wave filmmakers represent China in this age of neoliberal reform. Analyzing this paradigm shift in independent cinema, this text explores the historicity of the cinematic form and its cultural-political visions. Through a close reading of the narrative strategy of key films in New Wave Cinema, Xiaoping Wang studies the movement's impact on film, literature, culture and politics.